A case of ventricular tachycardia precipitated by caffeine: a rare occurrence - Kumar, Dharminder; Bhat, Sanjeev (International Journal of Research in Medical Sciences, 2019)
The effects of caffeine vary according to the dose and patient. Thus, there is no bright line defining thresholds. Here, we present an unusual case of ventricular tachycardia precipitated by a dose of 450-500 mg of caffeine in a healthy 33-year-old man.